PENGARUH LOCUS OF CONTROL, EMPLOYEE RELATIONS DAN UNSUR RELIGI DALAM MENINGKATKAN KINERJA KARYAWAN PT. BANK SYARIAH MANDIRI CFBC MEDAN - Supar Wasesa; Farid Fathony Ashal (Universitas Islam Negeri Sumatera Utara, 2017)
This study aims at determining the intensity of Locus of Control, Employee Relations, Salaries and religiosity influence on the performance of employees at PT. Bank Mandiri Syariah CFBC Medan. The population involved in this study were the employees of PT. Bank Mandiri Syariah CFBC Medan which amounted to 65 respondents. Data collection technique was complished by spreading the questionnaire to 65 respondents which comprised of 19 items for everyone and it was divided into 3 independent variables and a dependent variable. Furthermore, the interview was held to whom that was considered important in completing the research data, then all documentations study in the form of research object literature as well as direct observation were conducted to directly find out the activities of respondents. In the F statistical analysis, the locus of control, employees relations, and religiosity were simultaneously led to a positive effect in improving the performance of PT. Bank Mandiri Syariah CFBC Medan Employee.